Sprouty 2 protein, but not Sprouty 4, is an independent prognostic biomarker for human epithelial ovarian cancer. Issue 3 (29th January 2015) - Masoumi‐Moghaddam, Samar; Amini, Afshin; Wei, Ai‐Qun; Robertson, Gregory; Morris, David L.
<x xml:space="preserve">Abstract</x> Sprouty proteins are evolutionary‐conserved modulators of receptor tyrosine kinase signaling, deregulation of which has been implicated in the pathophysiology of cancer. In the present study, the expression status of Spry2 and Spry4 proteins and its clinical relevance in human epithelial ovarian cancer (EOC) were investigated retrospectively. We examined the immunohistochemical expression of Spry2 and Spry4 in matched tumor and normal tissue samples from 99 patients. The expression of ERK, p‐ERK, Ki67, fibroblast growth factor‐2, vascular endothelial growth factor and interleukin‐6 and their correlation with Sprouty homologs were also evaluated. Moreover, the correlation between Spry2 and Spry4 and the clinicopathological characteristics were analyzed along with their predictive value for overall survival (OS) and disease‐free survival (DFS). Our data indicated significant downregulation of Spry2 and Spry4 in tumor tissues (p < 0.0001). A significant inverse correlation was evident between Spry2 and p‐ERK/ERK (p = 0.048), Ki67 (p = 0.011), disease stage (p = 0.013), tumor grade (p = 0.003), recurrence (p < 0.001) and post‐treatment ascites (p = 0.001), individually. It was found that Spry2 low‐expressing patients had significantly poorer OS (p = 0.002) and DFS (p = 0.004) than those with high expression of Spry2. Multivariate analysis showed that high Spry2 (p = 0.018), low stage (p = 0.049) and no residual tumor (p =0.006) were independent prognostic factors for a better OS. With regard to DFS, high Spry2 (p = 0.044) and low stage (p = 0.046) remained as independent predictors. In conclusion, we report for the first time significant downregulation of Spry2 and Spry4 proteins in human EOC. Spry2 expression was revealed to significantly impact tumor behavior with predictive value as an independent prognostic factor for survival and recurrence.